Review of Energy Minimization Strategies for Eco friendly cloud in IT - kumari, Vasantha N; Murugan, Arul (International Journal of Computer Sciences and Engineering, 2025)
The usage of cloud is increasing in day to day life which leads to consumption of energy.Cloud Computing with reduced energy consumption has been an important topic for the era of researchers and different computer users of computing systems. Cloud IT is an egressing technology which provides information about communication technologies, proposing new challenges for environmental protection. Green Cloud computing is a component of Green IT. The amount of carbon will be reduced with low energy consumption. This paper outlines the methods to reduce energy consumption in the cloud. To reduce the power in cloud, huge numbers of evaluations and optimizations have been done for successful energy efficiency. There are different methods to implement the cloud with minimum energy consumption like hardware, software and firmware. Hardware method includes reduction of energy in various components of cloud like server, etc. Software includes virtualization techniques, DVFS techniques, etc. Energy has to be reduced to create Eco-friendly environment.